Electric Vehicle-Based Virtual Batteries in Power Distribution System Operation - Diaz-Cachinero, Pablo; Guldorum, Hilmi Cihan; Cuadra-Garcia, Alejandro; Munoz-Delgado, Gregorio; Contreras, Javier (IEEE, 2024)
Environmental concerns and the need for sustainable energy are transforming energy systems, highlighting the role of electric vehicles (EVs) and renewable energy sources in reducing the emissions in transportation and power distribution systems, respectively. In this paper, a scenario-based stochastic energy schedulingmodel for the power distribution system operation is proposed, considering the presence of EVs in the form of virtual batteries. This model also takes into account conventional generation, wind and solar generation, battery banks (BBs), and ac power flow. Furthermore, since an EV-based virtual battery is a system that combines the stored energy of some EVs to act as a single large battery, it is necessary to characterize its operation in terms of EV behavior. To that end, a probability-based methodology is developed to characterize the uncertain parameters of EV-based virtual batteries relying on historical data. Such parameters include initial energy, minimum and maximum energy limits, and net balance of energy entering and leaving the virtual battery, as well as the charging and discharging power limits. In addition, the uncertainty associated with renewable generation, demand, and prices is also considered. Finally, the proposed model is tested in the IEEE-37 bus system. Numerical results demonstrate the relevance of EVs for the operation of power distribution systems.
Keywords: Conic Power Flow; Distribution Systems; Electric Vehicle; Stochastic Programming; Virtual Battery; BIDDING STRATEGY; STORAGE; Computer Science; Science & Technology - Other Topics; Energy & Fuels; Engineering